Situation on Rodents Abundance and Epidemiological Situation on Tularemia in the Territory of the Russian Federation in the Second Half of 2014, and Prognosis for 2015 - D. V. Trankvilevsky; A. I. Udovikov; V. P. Popov; K. S. Zakharov; N. V. Popov; V. E. Bezsmertny (Проблемы особо опасных инфекций, 2015)
Analyzed are the data on the state of the carrier populations (abundance rates, distribution by stations) across constituent entities of the Russian Federation in 2014 as compared to the previous period. On the whole abundance of small mammals has not exceeded the long-term average annual values. For each of the 9 Federal Districts given has been an estimation of epizootic and epidemic activity in the natural tularemia foci in 2014. Outlined is a sharp decrease in tularemia morbidity in comparison to 2013. It is determined that within the past two decades there has occurred three major incidence outsurges in 1995, in 2005, and 2013, respectively. Based on the information obtained made has been the forecast for the development of epidemiological situation in natural tularemia foci of various types. Against the background of sharp decrease in the morbidity rates consequent upsurges are registered at certain intervals of several years, nevertheless current volatile state of ecosystems may draw a mixed response of parasitic systems.